2021
DOI: 10.5045/br.2021.2021094
|View full text |Cite
|
Sign up to set email alerts
|

Effects and treatment applications of polymeric nanoparticles on improving platelets' storage time: a review of the literature from 2010 to 2020

Abstract: Maintaining the quality of platelet products and increasing their storage time are priorities for treatment applications. The formation of platelet storage lesions that limit the storage period and preservation temperature, which can prepare a decent environment for bacterial growth, are the most important challenges that researchers are dealing with in platelet preservation. Nanotechnology is an emerging field of science that has introduced novel solutions to resolve these problems. Here, we reviewed the repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 92 publications
(144 reference statements)
0
3
0
Order By: Relevance
“…Some studies demonstrated increased platelet aggregation upon exposure to ligand-bearing liposomes such as PEG or Lewis x ( 48 ). Indeed, the surface of the nanoparticles is an important determining factor for interactions with platelets ( 49 , 50 ). Nevertheless, in the current study we show that platelets are equally capable of binding GM3 liposomes and control liposomes.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies demonstrated increased platelet aggregation upon exposure to ligand-bearing liposomes such as PEG or Lewis x ( 48 ). Indeed, the surface of the nanoparticles is an important determining factor for interactions with platelets ( 49 , 50 ). Nevertheless, in the current study we show that platelets are equally capable of binding GM3 liposomes and control liposomes.…”
Section: Discussionmentioning
confidence: 99%
“…Under these conditions, stopping bleeding and its control subsequently becomes an urgent task requiring a solution. Most topical agents are ineffective in conditions of hypocoagulation [2,7,8].…”
Section: Relevancementioning
confidence: 99%
“…Nanotechnology as an advancing science has provided new opportunities for studying not only the mechanisms of cell damage but also the development of efficient and safe methods for storing cells outside the body which offers a potential solution to the challenges of blood products storage and separation (Belousov et al 2019 ; Dashti Rahmat Abadi et al 2014 ; Mehrizi 2021a ; Shahabi et al 2014 ; Zadeh Mehrizi 2021a , b , c ; Zadeh Mehrizi and Amini Kafiabad 2021a , b ; Zadeh Mehrizi et al 2021 ; Zadeh Mehrizi and Eshghi 2021 ; Zadeh Mehrizi and Mousavi Hosseini 2021 ). Carbon nanoparticles have received much attention due to their particular optical, thermal, mechanical, electrical, and chemical features.…”
Section: Introductionmentioning
confidence: 99%